Regulation of Malignant Myeloid Leukemia by Mesenchymal Stem Cells - Tan, Zhenya; Kan, Chen; Wong, Mandy; Sun, Minqiong; Liu, Yakun; Yang, Fan; Wang, Siying; Zheng, Hong (Frontiers in Cell and Developmental Biology, 2022)
Bone marrow microenvironment (BMM) has been proven to have benefits for both normal hematopoietic stem cell niche and pathological leukemic stem cell niche. In fact, the pathological leukemia microenvironment reprograms bone marrow niche cells, especially mesenchymal stem cells for leukemia progression, chemoresistance and relapse. The growth and differentiation of MSCs are modulated by leukemia stem cells. Moreover, chromatin abnormality of mesenchymal stem cells is sufficient for leukemia initiation. Here, we summarize the detailed relationship between MSC and leukemia. MSCs can actively and passively regulate the progression of myelogenous leukemia through cell-to-cell contact, cytokine-receptor interaction, and exosome communication. These behaviors benefit LSCs proliferation and survival and inhibit physiological hematopoiesis. Finally, we describe the recent advances in therapy targeting MSC hoping to provide new perspectives and therapeutic strategies for leukemia.